Beneficial effect of insulin treatment on islet transplantation outcomes in Akita mice. - Kazuhide Kikawa; Daisuke Sakano; Nobuaki Shiraki; Tomonori Tsuyama; Kazuhiko Kume; Fumio Endo; Shoen Kume (PLoS ONE, 2014)
Islet transplantation is a promising potential therapy for patients with type 1 diabetes. The outcome of islet transplantation depends on the transplantation of a sufficient amount of β-cell mass. However, the initial loss of islets after transplantation is problematic. We hypothesized the hyperglycemic status of the recipient may negatively affect graft survival. Therefore, in the present study, we evaluated the effect of insulin treatment on islet transplantation involving a suboptimal amount of islets in Akita mice, which is a diabetes model mouse with an Insulin 2 gene missense mutation. Fifty islets were transplanted under the left kidney capsule of the recipient mouse with or without insulin treatment. For insulin treatment, sustained-release insulin implants were implanted subcutaneously into recipient mice 2 weeks before transplantation and maintained for 4 weeks. Islet transplantation without insulin treatment did not reverse hyperglycemia. In contrast, the group that received transplants in combination with insulin treatment exhibited improved fasting blood glucose levels until 18 weeks after transplantation, even after insulin treatment was discontinued. The group that underwent islet transplantation in combination with insulin treatment had better glucose tolerance than the group that did not undergo insulin treatment. Insulin treatment improved graft survival from the acute phase (i.e., 1 day after transplantation) to the chronic phase (i.e., 18 weeks after transplantation). Islet apoptosis increased with increasing glucose concentration in the medium or blood in both the in vitro culture and in vivo transplantation experiments. Expression profile analysis of grafts indicated that genes related to immune response, chemotaxis, and inflammatory response were specifically upregulated when islets were transplanted into mice with hyperglycemia compared to those with normoglycemia. Thus, the results demonstrate that insulin treatment protects islets from the initial rapid loss that is usually observed after transplantation and positively affects the outcome of islet transplantation in Akita mice.